Thin-Film Gd-Doped Ceria Sr-Barrier Layers for Electrolyte Supported SOFCs. (10th July 2019) - Han, Feng; Sata, Noriko; Riegraf, Matthias; Fuchs, Franz-Martin; Semerad, Robert; Geipel, Christian; Walter, Christian; Costa, Rémi
Abstract : In order to prevent detrimental reaction during manufacturing and enable the use of high performing La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) cathode in electrolyte supported solid oxide cells, Ce0.8 Gd0.2 O2-δ (GDC) barrier layer is implemented between the cathode and the electrolyte. It is of great interest to manufacture thin and dense GDC layer at low temperature to avoid unfavorable reactions. GDC layers deposited through Electron-Beam Physical Vapor Deposition (EB-PVD) were investigated to address this challenge. Dense GDC barrier layers of different thickness were deposited onto yttria-stabilized zirconia (YSZ) electrolyte. Samples coated with GDC thin-film, with and without LSCF cathode, were thermally treated to simulate further cell and stack processing steps. XRD and SEM were applied to evaluate the phase composition, thermomechanical stability, morphology and microstructural changes. It is found that the 0.5 µm GDC layer remains crack-free and adherent to the substrate after the simulated thermal cycles.